Frontispiece: Precursor Design Strategies for the Low‐Temperature Synthesis of Functional Oxides: It's All in the Chemistry. Issue 42 (27th July 2020) - Marchal, Wouter; De Sloovere, Dries; Daenen, Michael; Van Bael, Marlies K.; Hardy, An
Abstract : Limiting the energetic budget during the solution processing of oxides is one of the most crucial considerations, adhering to green chemistry principles. Low‐temperature strategies require thought‐out adjustments at the level of the chemical precursor system. Specific reagents can be added to trigger auto‐combustion reactions, influence the sol‐gel network, obtain UV‐sensitive precursors or to tune the intermediates/transition states during decomposition. The successful implementation will also open up novel applications in flexible electronics and hybrid materials. For more details see the Review by W. Marchal et al. on page 9070 ff.